Development of a micro-scale method to assess the effect of corrosion on the mechanical properties of a biodegradable Fe-316L stent material. (February 2021) - Frattolin, Jennifer; Cattarinuzzi, Emanuele; Rajagopalan, Sriraman; Gastaldi, Dario; Vena, Pasquale; Yue, Stephen; Bertrand, Olivier F.; Mongrain, Rosaire
Abstract: The application of biodegradable materials to stent design has the potential to transform coronary artery disease treatment. It is critical that biodegradable stents have sustained strength during degradation and vessel healing to prevent re-occlusion. Proper assessment of the impact of corrosion on the mechanical behaviour of potential biomaterials is important. Investigations within literature frequently implement simplified testing conditions to understand this behaviour and fail to consider size effects associated with strut thickness, or the increase in corrosion due to blood flow, both of which can impact material properties. A protocol was developed that utilizes micro-scale specimens, in conjunction with dynamic degradation, to assess the effect of corrosion on the mechanical properties of a novel Fe-316L material. Dynamic degradation led to increased specimen corrosion, resulting in a greater reduction in strength after 48 h of degradation in comparison to samples statically corroded. It was found that thicker micro-tensile samples (h > 200 μm) had a greater loss of strength in comparison to its thinner counterpart (h < 200 μm), due to increased corrosion of the thicker samples (203 MPa versus 260 MPa after 48 h, p = 0.0017). This investigation emphasizes the necessity of implementing physiologically relevant testing conditions, including dynamic corrosion and stent strut thickness, when evaluating potential biomaterials for biodegradable stent application. Graphical abstract: Image 1 Highlights: Development of micro-tensile protocol in conjunction with dynamic corrosion tests. Effect of corrosion on mechanical properties of Fe-316L influenced by specimen size. Dynamic degradation had greater impact than static corrosion environment. Thicker micro-samples had greater reduction in strength than thinner micro-samples.